Analisis Kualitas Pelayanan Untuk Meningkatkan Kepuasan Pelanggan Dengan Metode Quality Function Deployment (Studi Kasus PDAM Tirta Gemilang Unit Kalinegoro Kabupaten Magelang): Analysis of Service Quality to Increase Customer Satisfaction Using the Quality Function Deployment Method (Case Study of PDAM Tirta Gemilang, Kalinegoro Unit, Magelang Regency) - Widodo, Eko Muh; Affan Jazaul Haq, Muhammad; Imron Rosyidi, Muhammad; Rifai, Affan (Universitas Muhammadiyah Magelang, 2025)
PDAM Tirta Gemilang Unit Kalinegoro is one of the regional company units in Magelang Regency as a clean water provider that is responsible for developing and managing a clean water supply system. In an effort to serve customers, PDAM Tirta Gemilang Unit Kalinegoro received complaints from customers. This study aims to improve the quality of service according to customer needs. The study used the servqual approach and the Quality Function Deployment method. The results of this study found 4 attributes that were prioritized for improvement, namely notification when there was a disruption and repair (8.48), experienced officers (8.57), clean distributed water quality (8.59), speed of counter service (8.82). The priority of developing PDAM Tirta Gemilang Kalinegoro Unit to meet customer needs is by following the 2-stage QFD quality procedure sequence, namely providing training related to administrative skills (311.31), improving water treatment processes such as filtration and disinfection (223.44), maintaining and cleaning distribution networks (223.44), providing training related to operational procedures (197.37), providing training related to customer service (197.37), adding service counters (128.88), using social media such as Instagram and WhatsApp to provide notifications (124.74).